Developing a Social Marketing–Based Colorectal Cancer Screening Campaign Centered on Stool-Based Testing for Patients Utilizing Services at a Federally Qualified Healthcare Center. (June 2023) - Ewing, Aldenise Phylicia; Bewa, Marlene Joannie; Zemen, Rahel; Schneider, Tali; Zaire, Portia J.; Clark, Justice; Hefner, Jennifer; Parvanta, Claudia
Background: More than 50% of colorectal cancer (CRC)–related deaths could be prevented with early detection and treatment. Federally Qualified Healthcare Centers (FQHCs)—safety-net facilities that provide primary care services to uninsured, underinsured and minority patients—report some of the lowest CRC screening rates. Effective CRC screening interventions within FQHCs may help to promote CRC screening utilization among patients from diverse backgrounds. Focus of Article: This study was designed to explore average-risk, patient perceptions of facilitators and impediments of using the Fecal Immunochemical Test (FIT) kit for CRC screening within the social marketing framework of the 4 "P's"—product, price, place, and promotion. Research Aim: To conduct formative research with priority populations (i.e., diverse, FQHC patients), assess acceptability of the FIT kit, and identify ways to better meet preferences and needs. Program Design/Approach: Qualitative, Focus Groups. Importance to the Social Marketing Field: Findings from this study would aid in the future development of a community-based prevention marketing intervention to promote CRC screening within FQHCs that serve diverse patient populations. Methods: Focus groups were conducted in English and Spanish with CRC screening age-eligible patients from a South Florida FQHC System. Interview guides were designed to better understand FQHC patient perceptions of CRC Screening via the FIT kit (product) by up-to-date and not up-to-date participants. Additional topics included likes/dislikes (price), preferred location for completing CRC screening and receiving CRC prevention education (place), and strategies for persuasive communication to increase CRC screening among patients who visit FQHCs (promotion). Data were analyzed to identify FIT screening facilitators and impediments using thematic coding in MaxQDA. Results: Five focus groups, involving 36 participants aged 50 and older, were conducted. Over half of participants self-identified as Hispanic (36%) or non-Hispanic Black (28%). Key facilitators were the convenience and simplicity of at-home testing (product), presumed affordability of it compared to colonoscopy (price), and ability to return by mail (place). Participants also shared numerous strategies for promotion, including direct referral from Primary Care Providers, mass media campaigns, mailed or electronic reminders from the clinic, and peer advocacy events in churches. Recommendations for Research or Practice: Social marketing provides an adequate approach for developing a patient-centered campaign to promote CRC screening uptake at FQHCs. Future CRC screening promotional campaigns at FQHCs should build on the motivation that patients must prioritize their health by emphasizing the convenience of completing CRC screening at home with the capability of mailing it back. Clinics should also work to reduce patient responsibility by developing automated clinic system reminders to openly communicate with patients about CRC screening.